COMMON ISSUES IN POST-DISASTER RECONSTRUCTION (Malaysian Journal of Civil Engineering, 2018)
This paper examines the types, degrees and effects of disaster, presents the phases in post-disaster response, and describes the issues arisen during post-disaster reconstruction phase. Disasters considered in this paper are only the ones that had caused great loss in terms of human lives and facilities. These conditions require well-coordinated works in the reconstruction process. There are many issues arise in the reconstruction process, ranging from operational, personnel, ethical, and funding issues. The main purpose of the paper is to identify the problems commonly occurred in the post-disaster reconstruction for various types of disaster. This study is carried out as a basis or as an initial step to develop a framework, method, and technologies to improve efficiency and effectiveness of post-disaster project. The method of this study comprises literature review from other researches in post-disaster reconstruction.